Acrylamide in commercial potato crisps from Spanish market: Trends from 2004 to 2014 and assessment of the dietary exposure. (July 2015) - Mesías, Marta; Morales, Francisco J.
Highlights: Acrylamide content in potato crisps ranged from 108 to 2180 µg/kg (mean: 630 µg/kg). High variations were observed between batches for certain brands. Acrylamide content in potato crisps showed a decreased trend from 2004 to 2014. Exposure to acrylamide from potato crisps was estimated to be 0.035 µg/kg BW/day. Abstract: This research updates the acrylamide content of commercial potato crisps marketed in Spain with the aim to evaluate its trend since 2004. Two different batches of 40 potato crisps brands from 18 producers were analysed. Acrylamide content ranged from 108 to 2180 µg/kg, with an average value of 630 µg/kg and a median of 556 µg/kg. Data revealed a continuous decreased trend from 2004 to 2014. In 2014, potato crisps showed an average acrylamide content 14.6% lower than the previous report in 2009 and 57.6% lower than the first report in 2004. These data confirm the overall effectiveness in the mitigation strategies implemented by the Spanish industrial sector, although variations up to 80% were observed between a number of brands. However, 17.5% of the samples registered values higher than the indicative value recommended by European Commission for potato crisps. The dietary exposure of the Spanish population to this contaminant through potato crisps intake was estimated to be 0.035 µg/kg body weight/day. Although exposure has decreased over the last ten years, it is necessary to continue efforts to reduce acrylamide content in potato crisps since there is still margin for it.